2012
DOI: 10.1590/s0100-83582012000300025
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to ACCase inhibitors in Eleusine indica from Brazil involves a target site mutation

Abstract: -Eleusine indica (goosegrass) is a diploid grass weed which has developed resistance to ACCase inhibitors during the last ten years due to the intensive and frequent use of sethoxydim to control grass weeds in soybean crops in Brazil. Plant dose-response assays confirmed the resistant behaviour of one biotype obtaining high resistance factor values: 143 (fenoxaprop), 126 (haloxyfop), 84 (sethoxydim) to 58 (fluazifop). ACCase in vitro assays indicated a target site resistance as the main cause of reduced suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 19 publications
6
35
1
1
Order By: Relevance
“…Contrary to earlier classifications, numerous recent investigations have clearly shown that, with the exception of the D2078G and C2088R mutations that confer broad resistance to all herbicides tested, the levels of resistance depend on specific amino acid changes, the number of resistant alleles, weed species, plant growth stages and recommended field rates of herbicides. For instance, plants with the I2041N were found to be sensitive to cycloxydim in A. myosuroides but resistant in P. paradoxa.…”
Section: Mechanism Of Resistancecontrasting
confidence: 64%
“…Contrary to earlier classifications, numerous recent investigations have clearly shown that, with the exception of the D2078G and C2088R mutations that confer broad resistance to all herbicides tested, the levels of resistance depend on specific amino acid changes, the number of resistant alleles, weed species, plant growth stages and recommended field rates of herbicides. For instance, plants with the I2041N were found to be sensitive to cycloxydim in A. myosuroides but resistant in P. paradoxa.…”
Section: Mechanism Of Resistancecontrasting
confidence: 64%
“…The plastidic ACCase gene sequences from a total of nine individual plants surviving fluazifop‐P‐butyl or butroxydim were analysed in comparison with those of the susceptible plants. The primer pair ELEIN1781F/ELEIN1781R (Osuna et al ., ) amplified a 600 bp DNA fragment covering the known mutation site 1781, and the primer pair ELEIN2027f/ELEIN2027r amplified an 832 bp fragment with the known mutation sites 1999, 2027, 2041, 2078, 2088 and 2096. Sequence alignment revealed an amino acid substitution of Trp‐2027‐Cys in R individuals, resulting from a G to T change at the third position of the Trp codon (TGG).…”
Section: Resultsmentioning
confidence: 99%
“…(). Published primers (Osuna et al ., ) used to amplify two plastidic ACCase gene fragments in which point mutations known to confer ACCase herbicide resistance in plants have been identified (Délye & Michel, ; Powles & Yu, ; Beckie & Tardif, ). The PCR was conducted in a 25 μL volume that consisted of 1–2 μL containing 50–100 ng of genomic DNA, 0.5 μ m of each primer and 12.5 μL of 2× GoTaq Green Master Mix ® (Promega, Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluazifop Haloxyfop Cyhalofop Sethoxydim Clethodim Tepraloxydim (Powles and Yu, 2010;Osuna et al, 2012;Kukorelli et al, 2013) Cys2088Arg…”
Section: Eleusine Indicamentioning
confidence: 99%